(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the strengthening of circulating water of an oil refinery with various reagents: Na2PO4 + sulfone mixture; Na2PO4; Na2PO4 + sulfonal; Ca (OH) 2. The results of deep cleaning of mechanical impurities Nа2PО4 and Kuimozor circulating water from large dispersed and fine particles are presented. The question of the influence of the hydraulic resistance of the sediment formed during the filtration of contaminated water on the degree of purification is also raised.